A study of residential bedroom interiors for advance-stage cancer patients in palliative house care - Arsenio, Rolyna Francesca F.
The purpose of this study was to explore the integration of medical care design in the residential bedroom spaces of selected advance cancer patients in palliative care. Through non-probability sampling, five female respondents from Metro Manila, Bulacan, and Rizal were interviewed. Their bedroom spaces were observed and documented as well. Grounded theory was used to identify how conditions of advance cancer affect the users needs and the medical care design to create their current bedroom space. Based on the findings of the study, the main considerations of the selected respondents interviewed were ensuring the users comfort and safety, avoiding fear-evoking interior elements, and improving self-esteem through independence in their bedroom space. Based on experience-based design, their considerations were integrated in the bedroom space by providing accessible layout and space allocation, ergonomic furniture, safe and relaxing finishes, relaxing lighting, cooler ventilation, quiet environment, and a clean interior space. In addition, the needs of the respondents were the primary basis for the adaptation of medical care into their bedrooms. Although the respondents modified the bedrooms to cater to their needs by having maximized use of cooling air-conditioning system, high utilization of the bed for many of their activities, allocation of furniture pieces closer to the bed, addition of pillows or mattresses on the bed for extra comfort and safety, shutting down of windows, removal of dust-collecting personal items, having provisions for visitors, having less demand for lighting, and displaying personal and spiritual accessories, there was no transformations in the form of permanent and structural interior elements inside the bedroom. This was because permanent fixtures such as grab bars caused fear and depression to the respondents.